Removal of separated instruments from unfavourable locations: Case reports using the HBW ultrasonic ring or a surgical approach - Coaguila-Llerena, Hernán [UNESP]; Lazo-Quezada, Geraldine; Teves, Abel; Zevallos-Chávez, Marco; Faria, Gisele [UNESP] (Wiley, 2022)
Two patients were admitted to the dental clinic to evaluate two right mandibular first molars (both FDI no. 46). In Case 1, there was an accidental instrument separation, which was thought to have been bypassed; however, the instrument was located beyond the apical foramen, in the alveolar bone. The 1-week follow-up revealed that the fragment was close to the inferior alveolar nerve, thus allowing surgical removal to be performed. In Case 2, two separated instruments located in the apical third of the mesiobuccal and mesiolingual canals were removed using the HBW ultrasonic ring coupled to ISO 10 and 15 hand instruments. The 3-month and 1-year follow-ups (Case 1), and the 2-year and 3-year follow-ups (Case 2) showed a favourable evolution in both cases. It can be concluded that both the surgical approach and the HBW ultrasonic ring are viable options for the removal of separated instruments in unfavourable locations.
Keywords: accidents; endodontics; oral surgery; root canal preparation; root canal therapy